Kajian Teologis Tentang Gaya Hidup “Hedonisme” dalam Amsal 21:17 dan Yesaya 5:11 Serta Implikasinya Bagi Orang Kristen Masa Kini - Yosep Iswanto Padabang; Iwan Bambang (Sekolah Tinggi Teologi Tenggarong, 2021)
Looking for everything that is in accordance with the wishes and pleasing to the human heart (Hedonism) is something that is commonplace and is always attached to everyone, but in doing it humans need to be guided and controlled by a basis, which makes humans always supervised so they don't fall into their own desires and ultimately self-destruct. As in Christianity, human desires should be in accordance with God's wishes, and everything that pleases the human heart must also please God and glorify God. Then what about Christians today, are they still walking according to God's wishes or their own desires? The author uses descriptive qualitative methods, while related to theological studies in relation to the hedonistic lifestyle, the authors relate descriptive qualitative research in the context of phenomenology with qualitative methods that are library research. Which is to analyze the content of meaning contained in a narrative or text, in relation to the Scriptures, the author uses narrative analysis. And in the and it can be concluded that the Christian life should be under the life of love and continue to walk under the grace and covenant of God, so that Christians can avoid a lifestyle that only seeks worldly pleasures that are limited and ultimately lead to destruction